TAX AVOIDANCE AS A MODERATOR OF TAX RATE, LEVERAGE, DIVIDEND POLICY, FIRM SIZE, AND FIRM VALUE - Miladi Sutanti; Darmawati Muchtar; Rico Nur Ilham; Ghazali Syamni; Husaini; Jummaini (RADJA PUBLIKA, 2026)
This study examines the effects of effective tax rate, leverage, dividend policy, and firm size on firm value, with tax avoidance as a moderating variable, among food and beverage companies listed on the Indonesia Stock Exchange during 2020–2024. A quantitative panel-data design was applied to 57 companies selected through purposive sampling, producing 285 firm-year observations. Secondary data were obtained from annual financial reports and analyzed using EViews. Random effects models were selected for the direct-effect specifications, whereas the interaction model used fixed effects. The findings show that tax rate, dividend policy, firm size, and tax avoidance do not have significant direct effects on firm value. Leverage has a negative and significant effect at the 10% level. Tax avoidance does not moderate the relationship between tax rate and firm value, but it significantly weakens the relationships of leverage, dividend policy, and firm size with firm value. The results indicate that debt and tax-planning decisions should be evaluated jointly because aggressive tax avoidance can intensify the adverse market implications of financing and corporate-scale decisions.